Tingkat Keterampilan Renang Gaya Crawl Jarak 25 Meter Pada Siswa Kelas IV SD Negeri Ngupasan Kabupaten Purworejo Tahun 2022 (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the level of swimming skills in Crawl Style at a distance of 25 meters in fourth grade students of SD Negeri Ngupasan, Purworejo Regency in 2022. This research was started on June 9, 2022. This research is a quantitative descriptive study using a one-shot case study design. with data collection techniques through survey tests using research instruments. The subjects of this study were fourth grade students of SD Negeri Ngupasan Purworejo. Data analysis used descriptively analyzed data with percentages. The results of the research and discussion, obtained the overall percentage in the very good category there are 3 students (15%), for the good category there are 4 students (20%), the sufficient category is 8 students (40%), while the less category there are 4 students (20% ), and the last one in the very poor category amounted to 1 student (5%). But there are still students who are less skilled because of several obstacles such as fear, hyperactivity, lack of use of appropriate swimming techniques. The conclusion from the results of the study is that the Crawl Style Swimming Skill Level of 25 Meters in Grade IV Students at SD Negeri Ngupasan, Purworejo Regency in 2022 is in the sufficient category.